When Is EEG Indicated in Attention-Deficit/Hyperactivity Disorder? - TÜRKDOĞAN, DİLŞAD; BEKİROĞLU, GÜLNAZ NURAL; ZAİMOĞLU, SENNUR (SAGE PUBLICATIONS INC, 2015)
The authors investigated the parameters for predicting epileptiform abnormalities in a group of children diagnosed with attention-deficit/hyperactivity disorder (ADHD). The sample consisted of 148 subjects aged between 6 and 13 (8.76 +/- 1.26; 25.7% female) years. Subtypes of ADHD and comorbid psychiatric disorders were defined according to DSM-IV criteria. The Wechsler Intelligence Scale for Children-Revised was applied to all patients. Most of the subjects (89.2%) had wakefulness and sleep electroencephalography examinations lasting about one hour. The authors found out that the coexistence of speech sound disorder (odds ratio [OR] 3.90, 95% confidence interval [CI]: 1.61-9.48) and higher Digit Span test performance (OR 1.24, 95% CI: 1.06-1.44) predicted the presence of accompanying epileptiform abnormalities. The prevalence of epileptiform abnormalities was 26.4%, and they were frequently localized in the frontal (41%) and centrotemporal (28.2%) regions. Higher percentage of speech sound disorder co-occurrence (64%) in subjects with rolandic spikes suggests that epileptiform abnormalities associated with ADHD can be determined genetically at least in some cases. Pathophysiology of epileptiform abnormalities in ADHD might have complex genetic and maturational background.
Keywords: attention-deficit; hyperactivity disorder; epileptiform abnormalities; speech-sound disorder; digit span; rolandic spikes; DEFICIT-HYPERACTIVITY DISORDER; SPEECH SOUND DISORDER; EPILEPTIFORM DISCHARGES; READING-DISABILITY; ROLANDIC SPIKES; LANGUAGE IMPAIRMENT; INCREASED FREQUENCY; CONNERS PARENT; CHILDREN; ADHD